2011
DOI: 10.1128/iai.00205-11
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus cereus G9241 Makes Anthrax Toxin and Capsule like Highly Virulent B. anthracis Ames but Behaves like Attenuated Toxigenic Nonencapsulated B. anthracis Sterne in Rabbits and Mice

Abstract: Bacillus cereus G9241 was isolated from a welder with a pulmonary anthrax-like illness. The organism contains two megaplasmids, pBCXO1 and pBC218. These plasmids are analogous to the Bacillus anthracis Ames plasmids pXO1 and pXO2 that encode anthrax toxins and capsule, respectively. Here we evaluated the virulence of B. cereus G9241 as well as the contributions of pBCXO1 and pBC218 to virulence. B. cereus G9241 was avirulent in New Zealand rabbits after subcutaneous inoculation and attenuated 100-fold compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 41 publications
0
52
0
Order By: Relevance
“…We previously reported that live spores of dcG9241, a plasmidcured derivative of B. cereus G9241, is avirulent in mice (18). In a preliminary study, we found that vaccination with live dcG9241 spores completely protected A/J mice against i.n.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…We previously reported that live spores of dcG9241, a plasmidcured derivative of B. cereus G9241, is avirulent in mice (18). In a preliminary study, we found that vaccination with live dcG9241 spores completely protected A/J mice against i.n.…”
Section: Resultsmentioning
confidence: 94%
“…B. cereus G9241, which was isolated from a welder with pulmonary anthrax-like disease, contains the pXO1 homolog pBCXO1 and an unrelated megaplasmid, pBC210 (8). B. cereus G9241 produces PA, LF, and EF from the pBCXO1-carried genes pag, lef, and cya, respectively (8,18). In addition, pBCXO1 encodes an intact and functional operon required for hyaluronic acid capsule synthesis (19), and pBC210 contains an operon that is necessary for production of a putative tetrasaccharide capsule (8,18,19).…”
mentioning
confidence: 99%
“…Unlike B. anthracis, these B. cereus strains are not designated select agents, and their virulence and pathogenic strategies have only recently been investigated. Wilson and coworkers studied the virulence of B. cereus G9241 spores in a rabbit model of inhalational anthrax-like disease (44). In contrast to B. anthracis strain Ames, which causes lethal respiratory disease in rabbits at a dose of Ն1 ϫ 10 5 spores, only one out of seven rabbits infected with B. cereus G9241 spores succumbed to aerosol challenge; the moribund rabbit had received a dose of approximately 10 7 spores (44).…”
Section: Discussionmentioning
confidence: 99%
“…Wilson and coworkers studied the virulence of B. cereus G9241 spores in a rabbit model of inhalational anthrax-like disease (44). In contrast to B. anthracis strain Ames, which causes lethal respiratory disease in rabbits at a dose of Ն1 ϫ 10 5 spores, only one out of seven rabbits infected with B. cereus G9241 spores succumbed to aerosol challenge; the moribund rabbit had received a dose of approximately 10 7 spores (44). By using intranasal spore challenge of anesthetized C57BL/6 mice, those authors calculated an LD 50 of 6.3 ϫ 10 5 B. cereus G9241 spores.…”
Section: Discussionmentioning
confidence: 99%
“…When tested in mice with a peritoneal challenge model, B. cereus G9241 causes anthrax-like disease in a manner requiring genes for protective antigen (pagA, located on pBCXO1), BPS (bpsX-H on pBC218), and HA polysaccharides (hasACB on pBCXO1). Further, B. cereus G9241 causes respiratory anthrax-like disease in rabbits (41). Of note, B. cereus G9241 does not harbor the capBC-DAE genes, which are present on B. anthracis pXO2 (24,42).…”
Section: Discussionmentioning
confidence: 99%